ENHANCING SPARE PARTS SALES BY IMPROVED CUSTOMER SERVICE LEVELS MEASURED BY OTIF (ON-TIME IN-FULL) THROUGH NEW SUPPORT POINTS AND SUPPLY CHAIN DISTRIBUTION DESIGN: A CASE STUDY AT PT XYZ MEDAN BRANCH - Sandjaja, Edwin; Panjaitan, Togar Wiliater Soaloon; Nasution, Henry (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2024)
It was found that there are no support points at PT XYZ's Martabe Site, which led to a problem with customer service levels measured by OTIF (On-Time In-Full). This situation may delay delivery due to the long distance (367 km or 12 hours by land transportation) between Medan and Martabe. Low OTIF rates correspond with the limited availability of parts at PT XYZ. A company's ability to supply demand with its stock is the availability of parts. Consequently, customers purchase from competitors with parts that are ready on-site. This study has designed new support points based on accurate demand forecasting and a project feasibility assessment based on an Internal Rate of Return (IRR). As a result, new support points guaranteed the availability of parts to make the item In-Full and decrease lead time delivery to make the item On-Time. After building a new support point at the Martabe site, sales increased by 74% and contributed to a 44% growth in sales in the Medan area